Phytochemical profiling and antioxidant activity assessment of Bellevalia pseudolongipes via liquid chromatography-high-resolution mass spectrometry - Yolbaş,İdris (PeerJ, 2024)
Background Plant-derived drugs are often preferred over synthetic drugs because of their superior safety profiles. Phenolic compounds and flavonoids—major plant components—possess antioxidant properties. Limited research has been conducted on the bioactive compounds and biochemical properties of Bellevalia pseudolongipes (Asparagaceae), an important pharmacological species endemic to Turkey. Therefore, the chemical composition and antioxidant properties of B. pseudolongipes were investigated in this study. Methods The chemical composition of B. pseudolongipes was analyzed using liquid chromatography-high-resolution mass spectrometry, and radical scavenging and antioxidant activities were evaluated using DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid)) tests. Results Thirty-eight compounds were identified, including trans-cinnamic acid, caffeic acid, vitexin, schaftoside, orientin, and narirutin. B. pseudolongipes showed high antioxidant activity in antioxidant activity tests. Conclusion These findings provide novel insights into the potential utility of B. pseudolongipes in the pharmaceutical, food, and cosmetics industries, highlighted by its significant antioxidant capacity.
Keywords: Phytochemicals; Bellevalia pseudolongipes (Asparagaceae); Antioxidants